A Pragmatist Approach to the Mutual Recognition between Ethico-Political and Theological Discourses on Evil and Suffering - Pihlström, Sami (Political theology, 2019)
This paper considers what may be taken to be a hitherto somewhat neglected issue in political theology: how should the division, or dichotomy, between two rather different responses to the problem of evil and suffering - that is, the theological and the secular ethico-political approaches - be understood and (possibly) overcome? It is suggested that pragmatism can utilize the theory of recognition in bridging this gap between two apparently very different discourses on evil and suffering. It is further argued that an antitheodicist approach to the problem of evil and suffering ought to be developed across the board, both theologically and politically.